Wordsworth's metaphysical verse : geometry, nature, and form - Johnson, Lee M. (Heritage., 1982)
In this book, Professor Johnson demonstrates how Wordsworth employed geometrical patterns in the metrical construction of his verse and how the character of those patterns can be related to the poet's major philosophical values.